South by Southwest : Katherine Anne Porter and the burden of Texas history - Stout, Janis P. (University of Alabama Press, 2013)
An interdisciplinary study of Katherine Anne Porter's troubled relationship to her Texas origins and southern roots, this book offers a fresh look at the author and her work. More than thirty years after her death, Katherine Anne Porter remains a fascinating figure. Critics and biographers have portrayed her as a strikingly glamorous woman whose photographs appeared in society magazines. They have emphasized, of course, her writing - particularly the novel Ship of Fools, which was made into an award-winning film, and her collection Pale Horse, Pale Rider, which cemented her role as a significant and original literary modernist. They have highlighted her dramatic, sad, and fragmented personal life. Few, however, have addressed her uneasy relationship to her childhood in rural Texas. The author argues that throughout Porter’s life, she remained preoccupied with the twin conundrums of how she felt about being a woman and how she felt about her Texas origins. Her construction of herself as a beautiful but unhappy southerner sprung from a plantation aristocracy of reduced fortunes meant she construed Texas as the Old South. The Texas Porter knew and re-created in her fiction had been settled by southerners like her grandparents, who brought slaves with them. As she wrote of this Texas, she also enhanced and mythologized it, exaggerating its beauty, fertility, and gracious ways as much as the disaffection that drove her to leave. Porter's feelings toward Texas ran to both extremes, and she was never able to reconcile them.